2007
DOI: 10.1021/la0623432
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Formation and Self-Organization in a Simple Precipitation System

Abstract: Various types of pattern formation and self-organization phenomena can be observed in biological, chemical, and geochemical systems due to the interaction of reaction with diffusion. The appearance of static precipitation patterns was reported first by Liesegang in 1896. Traveling waves and dynamically changing patterns can also exist in reaction-diffusion systems: the Belousov-Zhabotinsky reaction provides a classical example for these phenomena. Until now, no experimental evidence had been found for the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 32 publications
2
73
0
2
Order By: Relevance
“…The instability often appears in the interface between a precipitation layer and the surrounding gel. The curvature (or the flatness) of the interface destabilizes, which results in the protrusion of a precipitation region from the interface [7][8][9][10]. The present authors found this type of instability for a counter-diffusion system [11], which was used by Putnis et al [3] to form chemical zoning in particle.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…The instability often appears in the interface between a precipitation layer and the surrounding gel. The curvature (or the flatness) of the interface destabilizes, which results in the protrusion of a precipitation region from the interface [7][8][9][10]. The present authors found this type of instability for a counter-diffusion system [11], which was used by Putnis et al [3] to form chemical zoning in particle.…”
Section: Introductionsupporting
confidence: 54%
“…Recently, macroscopic pattern formation of precipitation layers in gel has attracted much attention. Significant examples are a new type of the Liesegang pattern [10], chemical gardens [9], and a traveling wave [7,8] that appears to be observed for the Belouzov-Zabotinsky reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous appearance of travelling waves and spiral formation inside of the precipitation front was thus described for the first time. The dynamics and spatial structure of the observed traveling waves suggest the similar origin of BZ waves and the phenomena in [41]. The result in a real experiment is depicted in Figure 9.…”
Section: Simulation Results Discussionmentioning
confidence: 54%
“…Pattern formation phenomena in a precipitation system may produce similar structures. Our new experimental investigations [41] have shown the coexistence of precipitation process and excitability without any external forcing. Spontaneous appearance of travelling waves and spiral formation inside of the precipitation front was thus described for the first time.…”
Section: Simulation Results Discussionmentioning
confidence: 75%